Potential Biological Control Agents against Soft Rot Diseases Caused by Pectobacteria on Some Sugar Beet Cultivars - Mustafa Alparslan Umarusman; Kubilay Kurtuluş Baştaş (Turkish Journal of Agriculture: Food Science and Technology)
Sugar beet is one of the most economically important agricultural crops cultivated in many provinces of Turkey. Especially in recent years, there has been an increase in bacterial tuber rot due to factors related to climate change. In preliminary trials, soft rot disease by Pectobacterium caratovorum subsp. caratovorum (Pcc) and Pectobacterium betavasculorum (Pb) were detected predominantly in sugar beets in Central Anatolia. Today, some cultural measures and copper compounds are used against soft rot agents in sugar beet, but successful results cannot be obtained in preventing the disease. In this study, a total of 270 soil samples were taken from the rhizosphere of 10 different fields in 3 different periods in 3 different ecologically diverse districts (Çumra, Altınekin and Seydişehir) of Konya, one of the provinces with the highest amount of sugar beet production in Turkey. As a result of the isolations, a total of 3064 bacterial isolates were purified and 262 of them showed antibacterial activity against Pcc and Pb in vitro conditions. In addition, 15 antagonist bacteria with the highest inhibitory effect on the development of both pathogens were tested in greenhouse conditions, and according to the results obtained from here, 3 antagonists with the highest effect were tested in field conditions in the cultivation areas of 3 different districts named above. Biochemical, morphological and molecular diagnoses of antagonist bacteria with high efficacy were made. According to the results obtained, it has been concluded that rhizospheric bacteria with antagonistic effect have a success rate of 33-90% against Pcc and Pb pathogens, and that the biological products to be prepared in future studies can be used in ecological, climate friendly and within sustainable agricultural practices in sugar beet production areas.